Absorption Acid Gas Removal in Liquefied Natural Gas Process - Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Simulation of fluid mechanic of amine absorber process in removing acid gas from feed sour gas in LNG production plant is presented in this paper. The amine absorption in the Removing Acid Gas Process is designed to remove carbon dioxide, hydrogen sulfide and other sulfur compounds from the sour feed gas. The sour gas together with the recycle gas from the Treater unit enters the bottom of Amine Absorber and flows upward and passes through a demister pad to water wash section. In the Amine Absorber, the down-flowing amine solution absorbs and from the up-flowing sour gas to produce a sweetened gas stream as a product and an amine solution rich in the absorbed acid.